Development and Preparation of Oral Suspensions for Paediatric Patients - a Challenge for Pharmacists - Bruns Cornelia; Ober Michael (De Gruyter, 2018)
The preparation of liquid oral dosage forms for paediatric patients may pose a challenge on pharmacies. Marketed ready-to-use suspension vehicles do have advantages and disadvantages. In order to overcome the disadvantages a dedicated suspension vehicle, which can be prepared by every pharmacy, was cooperatively developed by pharmacist specialists on a national level in Germany. Marketed as well as pharmacy prepared suspension vehicles provide added value for pharmacy preparations for the special need of paediatric patients of different age groups.